A 17 year-old Boy with Urinary Retention: urinary retention - Dalirani, Reza; Khalili, Mitra; Mirzaee, Mahbubeh; Jamee, Mahnaz; Seifi, Atena (Journal of Pediatric Nephrology, 2021)
a 12-year old boy with urinary retention